2017
DOI: 10.3389/fmicb.2017.00314
|View full text |Cite|
|
Sign up to set email alerts
|

Identification and Characterization of miRNAs in Response to Leishmania donovani Infection: Delineation of Their Roles in Macrophage Dysfunction

Abstract: The outcome of Leishmania infection depends on parasite abilities to evade host immune response and its survival in hostile environment of host macrophages. Despite a wealth of gained crucial information, parasite strategies by which it dampens host macrophage functions remain poorly understood. Micro RNAs (miRNAs) are evolutionarily conserved class of endogenous 22-nucleotide small non-coding RNA gene products, described to participate in the regulation of almost every cellular process investigated so far. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
52
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 45 publications
1
52
0
1
Order By: Relevance
“…42 MiR-3620 has been reported to regulate the cell cycle, hypoxia, and zinc binding, as well as to play a key role in macrophage dysfunction. 43 Here, we observed that expression levels of miR-95-5p, miR-6776-5p, miR-3620-5p, and miR-4747-5p were sharply downregulated in HG-induced calcified/senescent HA-VSMCs. We found that lnc-ES3 also suppressed the expression of these four miRNAs in HG-induced calcified/senescent HA-VSMCs.…”
Section: Discussionmentioning
confidence: 61%
“…42 MiR-3620 has been reported to regulate the cell cycle, hypoxia, and zinc binding, as well as to play a key role in macrophage dysfunction. 43 Here, we observed that expression levels of miR-95-5p, miR-6776-5p, miR-3620-5p, and miR-4747-5p were sharply downregulated in HG-induced calcified/senescent HA-VSMCs. We found that lnc-ES3 also suppressed the expression of these four miRNAs in HG-induced calcified/senescent HA-VSMCs.…”
Section: Discussionmentioning
confidence: 61%
“…This wild type miRNA is also identified in our wild mice miRNA list having aggressive characteristics especially in controlling gene expression and can easily gain target site. In another interesting study, Tiwari et al, found out that mmu-mir-3473f, which belongs to wild mice category, is capable of regulating different biological processes associated with macrophage dysfunction in parasites 48 . The wild mice miRNAs seem to have a wide scoop for more analysis and various applications in genetics.…”
Section: Discussionmentioning
confidence: 99%
“…The initial steps of the inflammatory response occur during the phagocytosis of Leishmania and its establishment inside the phagolysosome and it is able to modulate the immune response by reducing the efficiency of inflammation and the development of an adaptive immune response [52][53][54][55]. Recent studies demonstrated that infections caused by L. amazonensis, L. infantum, L. major, and L. donovani can induce alteration in the miRNA profile from macrophages and dendritic cells of humans, murines, and dogs, thereby implicating the recognition and activation mechanisms of the immune response against parasites [56][57][58][59][60][61][62][63].…”
Section: Leishmania-host Interactionsmentioning
confidence: 99%
“…The L. donovani infection of THP-1 and human-MDM upregulates miR-30a levels and its inhibition increases the autophagic mechanism via negative regulation of Beclin 1 (BECN1), thereby decreasing infectivity [88]. Likewise, the L. donovani-infected murine macrophage expression of miRNA-3473f inhibits autophagy [63].…”
Section: Leishmania-host Interactionsmentioning
confidence: 99%